2011
DOI: 10.1016/j.indag.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Deformations of Lie brackets and representations up to homotopy

Abstract: We show that representations up to homotopy can be differentiated in a functorial way. A van Est type isomorphism theorem is established and used to prove a conjecture of Crainic and Moerdijk on deformations of Lie brackets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 5 publications
3
45
0
Order By: Relevance
“…In [16,17], it was shown that VB-groupoids and VB-algebroids provide an intrinsic version of the notion of (2-term) representation up to homotopy, generalizing the example given in the introduction, as well as Examples 2.5 and 2.9 above. In this section, we show how Theorem 2.14, when applied to 1-homogeneous cochains, recovers a Van Est result for the underlying 2-term representations up to homotopy of [4]. We also comment on how this approach realizes the original porposal in [11] for proving a rigidity conjecture.…”
Section: -Homogeneous Cochains and Representations Up To Homotopymentioning
confidence: 68%
See 3 more Smart Citations
“…In [16,17], it was shown that VB-groupoids and VB-algebroids provide an intrinsic version of the notion of (2-term) representation up to homotopy, generalizing the example given in the introduction, as well as Examples 2.5 and 2.9 above. In this section, we show how Theorem 2.14, when applied to 1-homogeneous cochains, recovers a Van Est result for the underlying 2-term representations up to homotopy of [4]. We also comment on how this approach realizes the original porposal in [11] for proving a rigidity conjecture.…”
Section: -Homogeneous Cochains and Representations Up To Homotopymentioning
confidence: 68%
“…Remark 3. 4. The conjecture was originally proved in [4] using a Van Est result for representations up to homotopy.…”
Section: Vb-groupoid and Vb-algebroid Cohomologymentioning
confidence: 99%
See 2 more Smart Citations
“…The second item deserves more attention. Note first that, as shown in [3], any 2-term representation up to homotopy of G(A) differentiates to a 2-term representation up to homotopy of A. In this case, one can see that G(A) ⋉ E integrates A ⋉ E, both as a groupoid and as a VB-groupoid [10].…”
Section: Lie Algebroid Representationmentioning
confidence: 99%